Religious Unemployment Eradication Strategy (Study in Pandeglang Regency Indonesia) Strategi Pengentasan Pengangguran Daerah Religi (Studi di Kabupaten Pandeglang, Indonesia - Agus Lukman Hakim (The Indonesian Journal of Public Administration (IJPA), 2022)
Pandeglang Regency community is an area that has a high level of religiosity. The high spirit of religion has positive and negative impacts. One negative impact is the development of a culture of fatalism, which has an impact on a low work ethic and the amount of underemployment. This study is a follow-up study that aims to analyze the problem of the reality of unemployment with a socioeconomic approach and analyze the priority of unemployment alleviation strategies in religious areas. This research is a descriptive research. Data collection techniques with expert judgment and interviews, through a purposive sampling method. Secondary data used from related institutions / agencies in the Regional Government of Pandeglang Regency. The analysis technique used withdescriptive analysis and Analytical Hyrarcy Process (AHP). The results showed thatThe priority strategy in reducing unemployment refers to the following criteria: First is increasing the competency of the workforce; Second, expansion of employment opportunities; Third, Development of the Labor Market; Fourth, population control.